Diseño de un Sistema de Control de Inventarios para la Granja Avícola Damiancito ubicada en la parroquia de Guaytacama, ciudad de Latacunga, provincia de Cotopaxi durante el período 2022 - Fernández Orozco, Paola Estefanía (2024)
This project was carried out with the objective of designing an inventory control system, which addresses the problem of managing records on the “Damiancito” agricultural farm in the Guaytacama parish, Latacunga, during the period 2022. To begin with, the foundation of the theoretical framework allowed us to support the different epistemic bases of the project, which was executed under a quantitative research approach based on numerical data, and with a field research modality. This methodology allowed us to take the necessary data to recognize the real state of the investigated subject. In addition, this research, which also had a descriptive mode, allowed us to determine an existing phenomenon with particular characteristics. Relevant data were obtained with the application of the interview technique to the manager and a group of workers. Thus, it was possible to identify shortcomings in inventory control. The results obtained in the analysis showed an amount of 680,392.50 in the inventory valuation in terms of stocks. Therefore, the FIFO (First In, First Out) control method will be applied to provide solutions, achieve optimization of the resources of the aforementioned company; and, in this way, they can correctly make decisions along with increase business productivity.